AI-Driven Ecosystems in Education Management: Redefining Institutional Agility and Stakeholder Engagement (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
Artificial Intelligence (AI) has emerged as a transformative force in education management, addressing operational inefficiencies, enhancing decision-making, and fostering stakeholder engagement. This study explores the dual role of AI-driven ecosystems in improving institutional agility and strengthening stakeholder interactions within diverse educational contexts. A mixed-methods approach was employed, combining a systematic literature review and case analysis across two institutions. The literature review identified key AI applications, including predictive analytics, adaptive learning, and real-time resource management, as pivotal in enabling institutions to respond to dynamic educational needs effectively. Case studies demonstrated measurable improvements, such as a 25% reduction in decision-making time and a 30% enhancement in administrative efficiency through chatbot integration. However, challenges like digital literacy gaps, infrastructure limitations, and algorithmic biases highlight the necessity for ethical governance and inclusive strategies. This research contributes to academic discourse by proposing actionable frameworks that integrate technological innovation with socio-ethical considerations. The findings emphasize the importance of adaptive and sustainable AI ecosystems in shaping equitable and future-ready educational institutions.